Role of cobalt and calcium on coal catalytic hydrogasification in a pressurized fluidized bed. (1st March 2019) - Qu, Xuan; Yan, Shuai; Yan, Xiaoqiang; Zhang, Jianshu; Zheng, Qi; An, Yingbao
Highlights: High coal conversion and CH4 yield could be simultaneously achieved in CCHG. Co-Ca catalyst triggered catalytic coal depolymerization and char hydrogasification. Individual Co and Ca had inferior catalytic activity towards coal hydrogasification. Ca retarded Co sintering, and more importantly initiated graphite carbon conversion. CH4 and tar yield could be moderated through varying catalyst loading. Abstract: Coal catalytic hydrogasification (CCHG) was carried out in a lab-scale pressurized fluidized bed to study the cobalt-calcium (Co-Ca) catalyst on the gross distribution of products by changing the addition amount of the catalyst. The CH4 formation behaviors and the structure properties of gasified coal char were analyzed to elucidate the role of Co and Ca in the dual catalyst system. Results show that 90.0 wt% of carbon conversion and 77.3 wt% of CH4 yield could be simultaneously achieved in 30 min with the help of 5%Co-1%Ca catalyst through hydrogasification at 850 °C and 3 MPa. Co-Ca dual catalyst triggered coal catalytic hydropyrolysis and coal char catalytic hydrogasification in succession. However, neither individual Co nor Ca had profound catalytic activity towards the condensed aromatic rings in coal structure. Co alone was prone to agglomerate during CCHG, resulting in the inactivation and blockage of the micropore structures. The addition of Ca retarded Co sintering and more importantly mediated Co-C interaction, making Co penetrating into the interior of coal matrix to accelerate the carbon conversion. The catalytic process of CCHG was summarized and the probable interaction between Co-Ca-C was discussed. The findings in this work will provide the theory foundation for the design of the catalyst in the pressurized fluidized bed gasifier.